Sistem Keamanan Kendaraan Jarak Jauh Menggunakan GPS Berbasis NODEMCU ESP8266 - Wahyu, Nurdi Dwi; Aryanto, Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The use of motorcycles as a means of personal transportation is a practical and easy-to-use transportation option in various crowded road conditions. In general, vehicle security systems are still very weak, and additional security systems are needed to prevent theft, especially in older vehicles. To increase security on motorbikes, researchers developed a security system that can monitor the location of motorbikes that can be monitored and controlled via an Android application. In making this prototype, the NodeMCU ESP8266 microcontroller as the Internet of Things (IoT), Ublox Neo-6M GPS module, and relays to control motorcycle electricity. The GPS module is used to determine the location based on the latitude and longitude of the motorcycle directly and will be sent to the server and then displayed through the Android application. In addition to displaying location coordinates, this application can also control motorcycle electricity with NodeMCU ESP8266 to activate relays connected to motorcycle electricity to function as turning on or off the motorcycle engine and there is a location history menu obtained from the GPS module.